2016
DOI: 10.1016/j.neuropsychologia.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Personal semantics: Is it distinct from episodic and semantic memory? An electrophysiological study of memory for autobiographical facts and repeated events in honor of Shlomo Bentin

Abstract: Declarative memory is thought to consist of two independent systems: episodic and semantic.Episodic memory represents personal and contextually unique events, while semantic memory represents culturally-shared, acontextual factual knowledge. Personal semantics refers to aspects of declarative memory that appear to fall somewhere in between the extremes of episodic and semantic. Examples include autobiographical knowledge and memories of repeated personal events. These two aspects of personal semantics have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 130 publications
7
73
0
Order By: Relevance
“…These results are perhaps most similar to the ones obtained in the Renoult et al (2015b) study, which found no differences in N400 amplitude to names of famous people associated with high and low levels of personal memories. Instead, the amount of personal episodic memories linked to a name modulated the later-occurring LPC, which is often associated with explicit recollection of contextual details (for reviews, see Rugg and Curran (2007) and Voss and Paller (2008)).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results are perhaps most similar to the ones obtained in the Renoult et al (2015b) study, which found no differences in N400 amplitude to names of famous people associated with high and low levels of personal memories. Instead, the amount of personal episodic memories linked to a name modulated the later-occurring LPC, which is often associated with explicit recollection of contextual details (for reviews, see Rugg and Curran (2007) and Voss and Paller (2008)).…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, our results replicate previous studies, described in the introduction, that have found greater P300/LPC responses to self-relevant information. Based on the results from Renoult et al’s (2015b) study, one possible interpretation of our data is that participants may be retrieving personal episodic memories associated with their personal preferences. Given these findings, a relevant question is the extent to which access to information about personal preferences involves the retrieval of both acontextual and episodic components.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, there is reason to believe that concepts with personal significance engage more than just the semantic memory system. Recent work suggests that these concepts may be more similar to episodic memory than general semantic memory (for a review, see Renoult, Davidson, Palombo, Moscovitch, & Levine, 2012), in that autobiographically significant concepts automatically activate related episodes in memory (Westmacott, Black, Freedman, & Moscovitch, 2004; Westmacott & Moscovitch, 2003) and evoke a neural signature more similar to episodic than semantic memory (Renoult et al, 2015, 2016). Thus, the current effects could be partly or entirely driven by episodic memory, with the names of familiar places activating related details of past episodes, including people who were there, in a relatively automatic (and potentially subconscious) manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, these two forms of memory are interdependent [48,49]. In particular, Renoult et al [49] introduced personal semantics (PS) memory. PS concerns knowledge of one's past and, like EM, PS is a personal feature (i.e.…”
Section: Episodic and Emotional Memory Binding (A) The Role Of Emotiomentioning
confidence: 99%